La pascua roja El primero de mayo de 1905 y los textos de la profanación - Espino Relucé, Gonzalo (2006)
This essay approaches, from a cultural stance, what happened during the Red Easter. The events refer to May 1 . 1905 and we present an analysis of the speeches delivered in that context as part of the conflict. Lima and Tarma are the places studied and the essay proposes that the Red Easter events were a symbol of profanation and shows the then existing relations between workers and intellectuals. st